(untitled) - Kroos, Kenneth A. (Stamford, 2015)
Presents a core course for disciplines in all four year engineering schools. This title helps Chemical and Biomedical engineering students to take courses in thermodynamics.
Nhiệt kỹ thuật
Keywords: Nhiệt động lực học,Thermodynamics